Sintered cermet, cermet tool, and cutting tool
By using the hard phase of TiCN and composite carbon nitride solid solution and the bonding phase of Co and Ni in the cermet sintered body, combined with the sintering process and coating layer design, the surface heat impact resistance in the prior art is solved. The problem is that high strength and wear resistance have been improved, and is suitable for harsh conditions such as wet intermittent cutting.
Patent Information
- Application Number
- CN202380046225.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
The existing cermet sintered bodies have shortcomings in improving the surface heat impact resistance, especially under harsh conditions such as wet interrupted cutting, it is difficult to simultaneously improve wear resistance and collapse resistance.
The first hard phase with TiCN as the main component and the composite carbon nitride solid solution of Groups 4, 5 and 6 of the periodic table are used as the second hard phase, and the bonded phase of Co and Ni is combined with the specific sintering process. The coating layer is designed to form a high-strength structure on the surface and inside to ensure that the average particle size of the second hard phase in the surface area is above 0.35 μm and below 0.6 μm and the intensity ratio is above 0.8.
The surface heat impact resistance and overall wear resistance of the cermet sintered body are significantly improved, ensuring the consistency of the strength of the surface and interior, and enhancing the performance stability under high thermal impact conditions.
Smart Images

Figure CN119278284A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cermet sintered body, a cermet tool and a cutting tool. Background Art
[0002] As a base body of a member requiring wear resistance, lubricity, and fracture resistance, such as a cutting tool, a wear-resistant member, and a lubricating member, a cermet sintered body containing titanium (Ti) as a main component is widely used.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 3099834 Summary of the invention
[0006] A sintered cermet according to one embodiment of the present invention comprises: a first hard phase having TiCN as a main component; a second hard phase being a composite carbonitride solid solution of at least one of the metals of Groups 4, 5 and 6 of the periodic table and Ti; and a binder phase containing at least one of Co and Ni and W. The average grain size d of the second hard phase in the inner region is 2in and the average particle size d of the second hard phase in the surface region 2sf The strength σ1 in the surface region and the strength σ2 in the internal region are both 2300 MPa or more, and the strength ratio of σ1 to σ2 (σ1 / σ2) is 0.8 or more. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 It is a perspective view showing an example of a cermet tool according to an embodiment.
[0008] Figure 2 It is a side cross-sectional view showing an example of the cermet tool according to the embodiment.
[0009] Figure 3 This is a schematic diagram of a scanning electron microscope photograph of a cross section of a sintered cermet body.
[0010] Figure 4 This is a front view showing an example of a cutting tool according to an embodiment.
[0011] Figure 5 This is a graph showing the bending strength in the surface region and the internal region of Sample No. 1 as a comparative example and Sample No. 3 as an example.
[0012] Figure 6 This is a graph showing the thermal shock strength of sample No. 1 as a comparative example and sample No. 3 as an example. DETAILED DESCRIPTION
[0013] Hereinafter, the method for implementing the sintered metal ceramic body, the metal ceramic tool and the cutting tool according to the present invention (hereinafter, recorded as "embodiment") is described in detail with reference to the accompanying drawings. It should be noted that the sintered metal ceramic body, the metal ceramic tool and the cutting tool according to the present invention are not limited to the present embodiment. In addition, the various embodiments can be appropriately combined within the scope that does not cause contradictions in the processing contents. In addition, the same reference numerals are marked on the same parts in the following embodiments, and repeated descriptions are omitted.
[0014] In the embodiments described below, there are cases where expressions such as "constant", "orthogonal", "perpendicular" or "parallel" are used, but these expressions do not need to be strictly "constant", "orthogonal", "perpendicular" or "parallel". That is, the above expressions allow for deviations in manufacturing accuracy, setting accuracy, etc.
[0015] In conventional cermet sintered bodies, there is room for further improvement in terms of improving the thermal shock resistance of the surface. Therefore, it is desired to provide a cermet sintered body, a cermet tool, and a cutting tool having high thermal shock resistance of the surface.
[0016] <Metal Ceramic Cutting Tools>
[0017] Figure 1 1 is a perspective view showing an example of a metal ceramic tool according to an embodiment. Figure 2 It is a side cross-sectional view showing an example of the cermet tool according to the embodiment. Figure 3 This is a schematic diagram of a scanning electron microscope photograph of a cross section of a sintered cermet body.
[0018] like Figure 1 as well as Figure 2 As shown, the cermet tool 1 of the embodiment includes a base body 2 and a coating layer 3 .
[0019] The substrate 2 has, for example, an upper surface and a lower surface ( Figure 1 The shape of the surface (the surface intersecting the Z axis shown) is a hexahedron of a parallelogram.
[0020] A corner portion of the substrate 2 functions as a cutting edge portion. The cutting edge portion has a first surface and a second surface connected to the first surface. The first surface is, for example, the upper surface of the substrate 2. The second surface is, for example, the side surface of the substrate 2. In an embodiment, the first surface functions as a "front face" for scraping off chips generated by cutting, and the second surface functions as a "flank face". A cutting edge is arranged on at least a portion of the ridgeline where the first surface and the second surface intersect, and the metal ceramic tool 1 cuts the workpiece by pressing the cutting edge against the workpiece.
[0021] A through hole 21 that penetrates the base 2 vertically may be arranged in the central portion of the base 2. In this case, a screw 75 (see FIG. 1 ) for attaching the metal ceramic tool 1 to the tool holder 70 described later is inserted into the through hole 21. Figure 4 ).
[0022] The base body 2 is composed of a sintered cermet body. The sintered cermet body contains Ti (titanium) and W (tungsten), and contains at least one of Co (cobalt) and Ni (nickel).
[0023] like Figure 3 As shown, the base 2 as a cermet sintered body contains a hard phase 5 and a binder phase 6. Specifically, the base 2 is obtained by bonding the hard phase 5 formed by solid-dissolving at least a portion of carbides, nitrides, and carbonitrides of at least one metal of Groups 4, 5, and 6 of the periodic table other than TiCN and Ti using the binder phase 6. The binder phase 6 contains at least one of Co and Ni and W.
[0024] The first hard phase is a hard phase having TiCN as a main component. In the present invention, the “main component” means, for example, 55% by mass or more when the entire hard phase of the constituent components is taken as 100% by mass.
[0025] Specifically, the first hard phase contains 80 wt% or more of Ti, 1 wt% or more and 15 wt% or less of W, and the total amount of one or more metals of periodic table Groups 4, 5, and 6. The first hard phase contains Co and / or Ni as the remainder.
[0026] The second hard phase is a hard phase composed of a composite carbonitride solid solution of at least one of the metals of Groups 4, 5, and 6 of the periodic table and Ti. Specifically, the second hard phase contains 30 wt% or more and 70 wt% of Ti, 70 wt% or more and 30 wt% or less of W and one or more metals of the metals of Groups 4, 5, and 6 of the periodic table, and a binder phase metal of 0 wt% or more and 3 wt% or less of Co and / or Ni in total.
[0027] like Figure 3 As shown in FIG. 1 , in an image of an arbitrary cross section of the cermet obtained by a scanning electron microscope (SEM), specifically, a reflected electron image, the first hard phase 5a is observed to be black relative to the second hard phase 5b, and the second hard phase 5b is observed to be grayish white relative to the first hard phase 5a. The second hard phase 5b also includes a second hard phase having a double core structure with the first hard phase 5a as the core and the second hard phase 5b as the peripheral portion. It should be noted that all second hard phases 5b do not need to have a core structure.
[0028] Here, the area centered at a position at a depth of 10 μm from the surface of the substrate 2 is defined as the surface area of the substrate 2, in other words, the sintered metal ceramic body. The width of the surface area in the depth direction of the substrate 2 may be, for example, 20 μm. In addition, the area centered at an arbitrary position at a depth of 0.4 mm or more from the surface of the substrate 2 is defined as the internal area of the substrate 2. The width of the internal area in the depth direction of the substrate 2 may be, for example, 20 μm.
[0029] In the substrate 2 of the embodiment, the average grain size d of the second hard phase 5b in the inner region is 2in and the average grain size d of the second hard phase 5b in the surface region 2sf The area ratio S of the second hard phase 5b in the inner region to the entire hard phase is 0.35 μm or more and 0.6 μm or less. 2in and the area ratio S of the second hard phase 5b in the surface region to the entire hard phase 2sf The strength σ1 in the surface region and the strength σ2 in the internal region are both 2300 MPa or more, and the strength ratio (σ1 / σ2) of the strength σ1 in the surface region to the strength σ2 in the internal region is 0.8 or more.
[0030] According to this structure, the surface strength of the sintered metal ceramic body can be improved while the increase in the Young's modulus of the metal ceramic surface can be reduced, thereby improving the thermal shock resistance of the surface of the metal ceramic. In particular, the wear resistance and fracture resistance of the metal ceramic can be improved under harsh conditions such as wet intermittent cutting that generate thermal shock.
[0031] In the substrate 2 of the embodiment, the average grain size d of the first hard phase 5a in the inner region is 1in and the average grain size d of the first hard phase 5a in the surface region 1sf The average grain size d of the first hard phase 5a in the inner region may be 0.25 μm or more and 0.35 μm or less. 1in and the average grain size d of the first hard phase 5a in the surface region 1sf The area ratio S of the first hard phase 5a in the inner region to the entire hard phase may be 0.25 μm or more and 0.3 μm or less. 1in and the area ratio S of the first hard phase 5a in the surface region to the entire hard phase 1sf The average grain size d of the first hard phase 5a in the surface region of the matrix 2 having this structure may be 20 area % or more and 35 area % or less. 1sf and the area ratio S 1sf is the average grain size d of the first hard phase 5a in the inner region1in And the area ratio S 1in Therefore, the thermal shock resistance of the surface can be improved to the same level as the thermal shock resistance of the inside.
[0032] For the substrate 2 of the embodiment, the hardness H1 in the surface region and the hardness H2 in the internal region may both be 1450 HV or more. In this case, the absolute value of the difference between the hardness H1 in the surface region and the hardness H2 in the internal region |H1-H2| may also be 50 or less. Since the hardness H1 in the surface region of the substrate 2 having this structure is equal to the hardness H2 in the internal region, the thermal shock resistance of the surface can be improved to the same degree as the thermal shock resistance of the internal region.
[0033] (Coating layer 3)
[0034] The coating layer 3 is applied to the substrate 2 for the purpose of improving the wear resistance, heat resistance, etc. of the substrate 2. Figure 2 In the figure, an example of a case where the coating layer 3 covers the surface of the substrate 2 as a whole is shown, but the coating layer 3 does not necessarily need to cover the entire surface of the substrate 2. The coating layer 3 is located on at least a portion of the surface of the substrate 2. When the coating layer 3 is located on the first surface of the substrate 2, which is the upper surface, the wear resistance and heat resistance of the first surface are high. When the coating layer 3 is located on the second surface of the substrate 2, which is the side surface, the wear resistance and heat resistance of the second surface are high.
[0035] The coating layer 3 may also be composed of, for example, at least one metal element selected from the elements of Groups 4, 5 and 6 of the periodic table, Al (aluminum) and Si (silicon), and at least one non-metal element selected from C (carbon), N (nitrogen) and O (oxygen). In the case of this structure, the oxidation resistance of the coating layer 3 is improved. As a result, the wear resistance of the coating layer 3 is further improved. The coating layer 3 may also be a single layer. In addition, the metal ceramic tool 1 may also have a coating layer 3 that is stacked in layers, i.e., two or more layers.
[0036] (Analysis method)
[0037] The above average particle size (d 1in d 2in d 1sf d 2sf ) and area ratio (S 1in , S 2in , S 1sf , S 2sf ) can be obtained, for example, by the following steps.
[0038] A cross section of the metal ceramic sintered body is photographed at 10,000 times magnification using a scanning electron microscope (SEM) to obtain a reflected electron image. The area including the position at a depth of 10 μm from the surface of the metal ceramic sintered body is defined as the surface area, and the area including the position at a depth of 400 μm from the surface of the metal ceramic sintered body is defined as the internal area. Alternatively, in each area, a straight line with a length of 10 μm is drawn in a direction parallel to the surface of the metal ceramic sintered body, and the diameter of each phase, specifically the particle size, and the existence ratio, specifically the area ratio, are calculated based on the length of the line segment crossing the first hard phase and the length of the line segment crossing the second hard phase.
[0039] Specifically, the value obtained by dividing the total length of the line segments crossing the first hard phase by the number of the first hard phases crossed by the line can be used as the average particle size of the first hard phase. Similarly, the value obtained by dividing the total length of the line segments crossing the second hard phase by the number of the second hard phases crossed by the line can be used as the average particle size of the second hard phase.
[0040] It should be noted that when calculating the average particle size of the first hard phase and the second hard phase, in order to avoid measurement deviation, the line segments smaller than a specific value can be excluded from the object. For example, 0.1 μm can be set as a specific value, and the first hard phase with the above-mentioned line segment being 0.1 μm or more is used as the first measurement object, and the total length of the line segment in the first measurement object is divided by the number of the first measurement objects crossed by the line, thereby calculating the average particle size of the first hard phase. Similarly, the second hard phase with the above-mentioned line segment being 0.1 μm or more is used as the second measurement object, and the total length of the line segment in the second measurement object is divided by the number of the second measurement objects crossed by the line, thereby calculating the average particle size of the second hard phase.
[0041] In addition, the ratio of the total length of the line segment crossing the first hard phase when the total sum of the length of the line segment crossing the second hard phase is set to 100% can also be calculated as the area ratio of the first hard phase. Similarly, the ratio of the total length of the line segment crossing the first hard phase when the total sum of the length of the line segment crossing the second hard phase is set to 100% can also be calculated as the area ratio of the second hard phase. At this time, the area of the bonding phase is excluded. In addition, the measurement is preferably performed by 3 fields of view, or the average can be taken. In addition, it can also be measured by using a commercially available image analysis device.
[0042] (Manufacturing method)
[0043] Next, a method for producing the base body 2 as a sintered body of cermet will be described.
[0044] In the manufacture of the sintered metal ceramic body of the present invention, TiCN powder is used. The raw material powder of TiCN can also be the raw material powder commonly used in the manufacture of metal ceramics. The raw material powder of TiCN can also be the raw material powder that has been subjected to a pulverizing process. In addition, when the raw material powder of TiCN is not the raw material powder that has been subjected to a pulverizing process, it is preferred to use a roller mill and a medium for pulverizing.
[0045] The raw material powder of TiCN is subjected to a pulverizing step, so that dislocations are generated inside the raw material powder of TiCN, and one or more metal elements among V, Nb, Ta, Cr, Mo, W, Co, and Ni move to positions where the dislocations exist.
[0046] It is preferable to use raw material powder of TiCN having such dislocations, carbides of the above-mentioned metals, and Co and Ni which serve as a binder phase as raw materials.
[0047] Using the raw material powder of TiCN having dislocations, the binder phase components such as Co and Ni may be set to 14 mass % or more and 22 mass % or less. When the binder phase components are set to the above range, the cermet as the matrix has high toughness and high hardness.
[0048] In addition, as the component containing V, Nb, Ta, Cr, Mo, and W, it is preferable to use the carbide of each metal element.
[0049] After the raw materials having the above-mentioned composition are mixed, sintering is performed. The sintering step can also be set as the following flow, for example.
[0050] (a) Process of heating from room temperature to 1100°C in a vacuum
[0051] (b) Step of maintaining the temperature at 1100°C in a vacuum for 1 to 2.5 hours
[0052] (c) A process of introducing N2 gas into the sintering furnace at 1100°C, changing the pressure in the sintering furnace to a pressure P1 of 5 Pa, and then raising the temperature from 1100°C to a temperature T1 of 1150 to 1300°C at a heating rate r1 of 0.1 to 2°C / min.
[0053] (d) Step of maintaining the temperature T1 for 0.5 to 2 hours
[0054] (e) A step of changing the pressure in the sintering furnace from the temperature T1 to the pressure P2 which is 300 to 2000 Pa higher than the pressure P1, and then raising the temperature from the temperature T1 to the temperature T2 which is 1300 to 1450° C. at a heating rate r2 of 1 to 5° C. / min.
[0055] (f) Step of maintaining the temperature T2 for 0.25 to 1.5 hours
[0056] (g) a step of changing the pressure in the sintering furnace to a pressure P3 which is 30 to 1000 Pa lower than the pressure P2, and then raising the temperature from the temperature T2 to the temperature T3 of 1450 to 1600° C. at a heating rate r3 of 2 to 10° C. / min.
[0057] (h) Process of maintaining temperature T3 for 1 hour
[0058] Specifically, after 0.25 hours had passed, the pressure in the calcining furnace was gradually reduced from the pressure P3 to 5 Pa over 0.25 hours. Thereafter, the pressure was maintained at 5 Pa for 0.5 hours.
[0059] (i) A step of changing the atmosphere to an Ar gas atmosphere of a pressure P4 of 10000 Pa to 80000 Pa while cooling the temperature from the temperature T3 to a temperature T4 of 100° C. or less at a cooling rate r4 of 10 to 50° C. / min.
[0060] The sintered cermet of the present invention can be produced by firing the molded body having the above-mentioned composition in the above-mentioned firing step.
[0061] After that, a coating layer 3 may be provided as needed. The coating layer 3 may be a so-called hard film, and is preferably formed by, for example, a PVD method or a CVD method. The coating film may be a single layer or a laminated film.
[0062] <Cutting tools>
[0063] Next, refer to Figure 4 The structure of a cutting tool including the above-mentioned cermet tool 1 will be described. Figure 4 This is a front view showing an example of a cutting tool according to an embodiment.
[0064] like Figure 4 As shown, the cutting tool 100 of the embodiment includes a cermet tool 1 and a tool holder 70 for fixing the cermet tool 1 .
[0065] The handle 70 is a rod-shaped member extending from the first end toward the second end. Figure 4 The first end is the upper end in Fig. 7, and the second end is the lower end in Fig. 7. The shank 70 is made of, for example, steel or cast iron. In particular, it is preferred to use steel having higher toughness among these components.
[0066] The tool handle 70 has a tool groove 73 at the end of the first end side. The tool groove 73 is a portion for assembling the metal ceramic tool 1, and has a seating surface intersecting with the rotation direction of the cut piece and a restraining side surface inclined relative to the seating surface. A screw hole for screwing a screw 75 described later is provided on the seating surface.
[0067] The metal ceramic tool 1 is located in the knife groove 73 of the knife handle 70 and is assembled to the knife handle 70 by means of a screw 75. That is, the screw 75 is inserted into the through hole 21 of the metal ceramic tool 1, and the front end of the screw 75 is inserted into the threaded hole formed on the seating surface of the knife groove 73 so that the threaded parts are screwed together. Thus, the metal ceramic tool 1 is assembled to the knife handle 70 in a manner that the cutting edge portion protrudes outward from the knife handle 70.
[0068] In the embodiment, a cutting tool used in so-called turning processing is illustrated. As turning processing, for example, inner diameter processing, outer diameter processing and slotting processing can be cited. It should be noted that the cutting tool is not limited to the cutting tool used in turning processing. For example, the metal ceramic tool 1 can also be used as a cutting tool used in milling processing. As the cutting tool used in milling processing, for example, milling cutters such as flat milling cutters, front milling cutters, side milling cutters, slotting milling cutters, single-edge end mills, multi-edge end mills, tapered edge end mills, ball-end mills, etc. can be cited.
[0069] Example
[0070] Hereinafter, examples of the present invention will be described in detail. It should be noted that the present invention is not limited to the examples shown below.
[0071] Samples No. 3 and No. 4 were produced as cermet sintered bodies by the above-mentioned production method. Samples No. 3 and No. 4 are examples of the present invention. Samples No. 1 and No. 2 are conventional cermet sintered bodies and are comparative examples.
[0072] The above-mentioned analytical method was used to calculate the average particle size and area ratio of the first hard phase and the second hard phase for the surface area and the internal area of each sample No. 1 to No. 4. It should be noted that in this calculation, the lower limit of the measurement object was set to 0.1 μm as mentioned above. The results are shown in Table 1.
[0073] [Table 1]
[0074]
[0075] The average grain size of the first hard phase in Sample No. 1 was 0.22 μm in the surface region and 0.31 μm in the internal region. The average grain size of the first hard phase in Sample No. 2 was 0.29 μm in the internal region. The average grain size of the first hard phase in Sample No. 3 was 0.29 μm in the surface region and 0.3 μm in the internal region. The average grain size of the first hard phase in Sample No. 4 was 0.26 μm in the surface region and 0.34 μm in the internal region.
[0076] The area ratio of the first hard phase in sample No. 1 was 12% in the surface area and 36.8% in the inner area. The area ratio of the first hard phase in sample No. 2 was 0% in the surface area and 4.3% in the inner area. The area ratio of the first hard phase in sample No. 3 was 28.7% in the surface area and 30.1% in the inner area. The area ratio of the first hard phase in sample No. 4 was 19% in the surface area and 51% in the inner area.
[0077] The ratio of the average grain size of the first hard phase in the surface region to the average grain size of the first hard phase in the internal region was 0.7 for sample No. 1, 0.95 for sample No. 3, and 0.76 for sample No. 4. The ratio was obtained by surface average grain size / internal average grain size.
[0078] The average grain size of the second hard phase in Sample No. 1 was 0.95 μm in the surface region and 0.48 μm in the internal region. The average grain size of the second hard phase in Sample No. 2 was 0.91 μm in the surface region and 0.85 μm in the internal region. The average grain size of the second hard phase in Sample No. 3 was 0.41 μm in the surface region and 0.51 μm in the internal region. The average grain size of the second hard phase in Sample No. 4 was 0.36 μm in the surface region and 0.58 μm in the internal region.
[0079] The area ratio of the second hard phase in sample No. 1 is 88% in the surface area and 63.2% in the inner area. The area ratio of the second hard phase in sample No. 2 is 100% in the surface area and 95.7% in the inner area. The area ratio of the second hard phase in sample No. 3 is 71.3% in the surface area and 69.9% in the inner area. The area ratio of the second hard phase in sample No. 4 is 81% in the surface area and 49% in the inner area.
[0080] The ratio of the average grain size of the second hard phase in the surface region to the average grain size of the second hard phase in the inner region was 1.98 for Sample No. 1, 1.07 for Sample No. 2, 0.8 for Sample No. 3, and 0.62 for Sample No. 4.
[0081] In addition, for the average particle size of the entire hard phase combining the first hard phase and the second hard phase, sample No. 1 is 0.64 μm in the surface area and 0.39 μm in the internal area, sample No. 2 is 0.91 μm in the surface area and 0.85 μm in the internal area, sample No. 3 is 0.36 μm in the surface area and 0.42 μm in the internal area, and sample No. 4 is 0.34 μm in the surface area and 0.46 μm in the internal area.
[0082] Thus, for samples No. 3 and No. 4 as examples, the average grain size d of the second hard phase in the inner region is 2in and the average particle size d of the second hard phase in the surface region 2sf In addition, for Sample No. 3 as an example, the area ratio S of the second hard phase in the inner region to the entire hard phase is 2in and the area ratio S of the second hard phase in the surface region to the entire hard phase 2sf The area ratio is 50% or more and 80% or less.
[0083] In addition, for samples No. 3 and No. 4 as examples, the average grain size d of the first hard phase in the inner region is 1in and the average particle size d of the first hard phase in the surface region 1sf In addition, for Sample No. 3 as an example, the area ratio S of the first hard phase in the inner region to the entire hard phase is 1in and the area ratio S of the first hard phase in the surface region to the entire hard phase 1sf The percentages were all greater than 20 area % and less than 35 area %.
[0084] From these results, it can be seen that the second hard phase in the surface region of Samples No. 3 and No. 4 as examples is finer than that of Samples No. 1 and No. 2 as comparative examples. On this basis, it can be seen that the difference in the grain size of the hard phase between the surface region and the internal region, specifically the first hard phase and the second hard phase, is smaller in Samples No. 3 and No. 4 as examples than in Samples No. 1 and No. 2 as comparative examples.
[0085] The thermal conductivity, Young's modulus, thermal expansion coefficient, hardness, and flexural strength of Samples No. 1 to No. 4 were measured. The results are shown in Table 2.
[0086] [Table 2]
[0087]
[0088] It should be noted that the thermal conductivity (λ) can be obtained according to JIS R 1611. The Young's modulus (E) can be obtained according to ISO14577. The thermal expansion coefficient (α) can be obtained according to JIS R 1618. The hardness can be obtained according to JIS R 1610. The bending strength can be obtained according to JIS R 1601. The strength test pieces were prepared as follows and used for the bending strength test of the surface area and the internal area. The internal strength test piece (size: 4mm*5mm*40mm) was ground off 0.5mm on each surface of the rectangular sintered body. The surface strength test piece (size: 4mm*5mm*40mm) was ground off 0.5 to 1mm on each surface of the rectangular body except the tension surface. In addition, in order to have the same shape as the tool surface, the tension surface of each strength test piece was blasted and polished to a few μm to 10μm, and a 3mm*4mm*40mm test piece was prepared.
[0089] In addition, the thermal shock strength (R 1c ). Thermal shock strength R 1c By R 1c =(λσ) / Eα. In addition, "ΔHV20" shown in Table 2 is the absolute value of the difference between the hardness H1 in the surface area and the hardness H2 in the internal area |H1-H2|. It should be noted that "HV20" means the hardness when measured with a test force of 20 kgf.
[0090] For sample No. 3 as an example, the bending strength σ1 in the surface area is 2449 MPa, and the bending strength σ2 in the internal area is 2512 MPa. In addition, for sample No. 3, the strength ratio of the bending strength σ1 to the bending strength σ2 (σ1 / σ2) is 0.97. It should be noted that the bending strength σ1 is the surface strength, and the bending strength σ2 is the internal strength.
[0091] In Sample No. 4 as an example, the bending strength σ1 in the surface region was 2450 MPa, and the bending strength σ2 in the internal region was 2350 MPa. In Sample No. 4, the strength ratio (σ1 / σ2) of the bending strength σ1 to the bending strength σ2 was 1.04.
[0092] Thus, for samples No. 3 and No. 4 as examples, the bending strength σ1 in the surface region and the bending strength σ2 in the internal region are both 2300 MPa or more, and the strength ratio (σ1 / σ2) of the bending strength σ1 to the bending strength σ2 is 0.8 or more. From this result, it can be seen that for samples No. 3 and No. 4 as examples, the strength in the internal region is relatively high, and the strength in the surface region is also high to the same degree as the strength in the internal region.
[0093] In addition, for sample No. 3 as an example, the hardness H1 in the surface region was 1531 HV20, and the hardness H2 in the internal region was 1495 HV20. In addition, ΔHV20 was 36 HV.
[0094] Thus, for sample No. 3 as an example, the hardness H1 in the surface region and the hardness H2 in the internal region are both 1450 HV or more, and the absolute value of the difference between the hardness H1 and the hardness H2 |H1-H2| is less than 50. From this result, it can be seen that for sample No. 3 as an example, the hardness in the surface region is at the same level as the hardness in the internal region.
[0095] In addition, for sample No. 4 as an example, the hardness H1 in the surface region was 1560 HV20, and the hardness H2 in the internal region was 1450 HV20. In addition, ΔHV20 was 110 HV.
[0096] In addition, for sample No. 3 as an example, the thermal shock strength in the surface region was 9783, and the thermal shock strength in the internal region was 10105. In addition, for sample No. 4 as an example, the thermal shock strength in the surface region was 9795, and the thermal shock strength in the internal region was 9549. On the other hand, for sample No. 1 as a comparative example, the thermal shock strength in the surface region was 5922, and the thermal shock strength in the internal region was 10309. In addition, for sample No. 2 as a comparative example, the thermal shock strength in the surface region was 7970, and the thermal shock strength in the internal region was 8274. Thus, it can be seen that the thermal shock strength in the surface region of samples No. 3 and No. 4 as examples is improved compared with samples No. 1 and No. 2 as comparative examples.
[0097] In addition, a fracture resistance test was performed on each of Samples No. 1 to No. 4. The conditions of the fracture resistance test were as follows.
[0098] <Fracturing resistance test (turning)>
[0099] Workpiece: S45C (25mm wide grooves × 4)
[0100] Cutting speed: 250m / min
[0101] Feed: 0.25mm / rev
[0102] Cutting depth: 0.5mm
[0103] Cutting state: wet
[0104] Evaluation method: Number of impacts until collapse (times)
[0105] As shown in Table 2, the number of impacts until the fracture was 8464 for sample No. 1 as a comparative example and 9141 for sample No. 2, whereas it was 11040 for sample No. 3 as an example and 10070 for sample No. 4. From this result, it can be seen that the fracture resistance of samples No. 3 and No. 4 as examples is improved compared with samples No. 1 and No. 2 as comparative examples.
[0106] Figure 5 Graphs showing the bending strength in the surface region and the inner region of sample No. 1 as a comparative example and sample No. 3 as an example. Figure 5 In the figure, the vertical axis shows the strength ratio when the bending strength in the inner region is set to 100%. Figure 6 Graph showing the thermal shock strength of sample No. 1 as a comparative example and sample No. 3 as an example. Figure 6 In FIG. 1 , the vertical axis shows the strength ratio when the thermal shock strength in the surface region of sample No. 1 is set to 100%.
[0107] like Figure 5 As shown in FIG. 1 , it can be seen that the difference between the bending strength in the surface region and the bending strength in the internal region of Sample No. 3 as an example is smaller than that of Sample No. 1 as a comparative example. Figure 6 As shown, it is known that the thermal shock strength in the surface region of Sample No. 3 as an example is improved compared with Sample No. 1 as a comparative example. Specifically, it is known that the thermal shock strength in the surface region of Sample No. 3 as an example is about 1.65 times higher than that of Sample No. 1 as a comparative example.
[0108] As described above, the sintered metal ceramic body (for example, the base body 2) of the embodiment includes: a first hard phase (for example, the first hard phase 5a) having TiCN as a main component; a second hard phase (for example, the second hard phase 5b) being a composite carbonitride solid solution of at least one of the metals of Groups 4, 5, and 6 of the periodic table and Ti; and a binder phase (for example, the binder phase 6) containing at least one of Co and Ni and W. The average grain size d of the second hard phase in the inner region is 2in and the average particle size d of the second hard phase in the surface region 2sf The strength σ1 in the surface region and the strength σ2 in the internal region are both 2300 MPa or more, and the strength ratio of σ1 to σ2 (σ1 / σ2) is 0.8 or more.
[0109] Therefore, according to the sintered cermet of the embodiment, the thermal shock resistance of the surface can be improved.
[0110] It should be noted that Figure 1 The shape of the metal ceramic tool 1 shown is an example and does not limit the shape of the metal ceramic tool according to the present invention. The metal ceramic tool according to the present invention may also have, for example: a rod-shaped body having a rotation axis and extending from a first end to a second end; a cutting edge located at the first end of the body; and a groove extending in a spiral from the cutting edge toward the second end of the body.
[0111] In addition, here, an example in which the sintered cermet is used as a cutting tool is described, but the use of the sintered cermet according to the present invention is not limited to cutting tools.
[0112] Further effects and variations can be easily derived by those skilled in the art. Therefore, the broader scheme of the present invention is not limited to the specific detailed and representative embodiments shown and described above. Therefore, various changes can be made without departing from the spirit or scope of the concept of the general invention defined by the attached technical solutions and their equivalents.
[0113] Description of Reference Numerals
[0114] 1 Metal ceramic cutting tools
[0115] 2 Matrix
[0116] 3 Coating layer
[0117] 5 Hard phase
[0118] 5a The first hard phase
[0119] 5b Second hard phase
[0120] 6 Adhesive phase
[0121] 21 Through hole
[0122] 70 Handle
[0123] 73 Slot
[0124] 75 Screws
[0125] 100 Cutting tools.
Claims
1. A sintered metal ceramic body, wherein: The metal ceramic sintered body comprises: The first hard phase has TiCN as a main component; A second hard phase, which is a composite carbonitride solid solution of at least one of the metals of Groups 4, 5, and 6 of the periodic table and Ti; and A binder phase comprising at least one of Co and Ni and W, The average particle size d of the second hard phase in the inner region 2in and the average particle size d of the second hard phase in the surface region 2sf All of them are 0.35μm or more and 0.6μm or less. The intensity σ1 in the surface region and the intensity σ2 in the internal region are both 2300 MPa or more, and the intensity ratio of σ1 to σ2 (σ1 / σ2) is 0.8 or more.
2. The cermet sintered body according to claim 1, wherein: The area ratio S of the second hard phase in the inner region to the entire hard phase is 2in and the area ratio S of the second hard phase in the surface region relative to the entire hard phase 2sf The area ratio is 50% or more and 80% or less.
3. The cermet sintered body according to claim 1, wherein: The average grain size d of the first hard phase in the inner region 1in and the average grain size d of the first hard phase in the surface region 1sf All of them are 0.25μm or more and 0.35μm or less. The area ratio S of the first hard phase in the inner region to the entire hard phase is 1in and an area ratio S of the first hard phase in the surface region relative to the entire hard phase 1sf The percentages were all greater than 20 area % and less than 35 area %.
4. The cermet sintered body according to claim 1, wherein: The hardness H1 in the surface area and the hardness H2 in the inner area are both 1450 HV or more, The absolute value of the difference between H1 and H2 |H1−H2| is 50 or less.
5. A metal ceramic tool, wherein: The metal ceramic tool has: The cermet sintered body according to any one of claims 1 to 4; and One or more coating layers are located on at least a portion of the surface of the metal-ceramic sintered body and are composed of at least one metal element selected from Groups 4, 5 and 6 of the periodic table, Al and Si, and at least one non-metal element selected from C, N and O.
6. A cutting tool, wherein: The cutting tool has: a knife handle extending from the first end toward the second end and having a knife groove on the side of the first end; and The metal ceramic cutting tool according to claim 5, which is located in the cutting groove.